TECHNICAL ANALYSIS IN PREDICTING STOCK PRICES MOVEMENT AND TESTING EFICIENT MARKET HYPOTHESIS IN INDONESIAN STOCK EXCHANGE - Sri Murtiasih; Ferry Ferdian (Universitas Gunadarma, 2012)
This study aims to evaluate the use of technical analysis in predicting stock price movements in Indonesia Stock Exchange (ISE). The study also aimed to determine the implications of technical analysis of the efficiency of information on the Stock Exchange. The population in this study are listed companies on the Stock Exchange from 2006-2010. The data used in this study is the stock price data during the observation period with the yield on the shares of profits (losses) of capital. Wilcoxon sign rank test used to differentiate stock returns using technical analysis with a passive investment strategy. The results suggest that technical analysis is useful for predicting stock price movements on the Stock Exchange in the future. Furthermore, this result is an early indication that ISE is not weak form efficient market. In other words ISE is an inefficient market based on information. Key Words: technical analysis, eficient market hypothesis, stock price, Indonesian Stock Exchange.